The effects of the histone deacetylase inhibitor 4-phenylbutyrate on gap junction conductance and permeability - Kaufman, Joshua; Gordon, Chris; Bergamaschi, Roberto; Wang, Hong Z.; Cohen, Ira S.; Valiunas, Virginijus; Brink, Peter (Frontiers in Pharmacology, 2013)
Longitudinal resistance is a key factor in determining cardiac action potential propagation. Action potential conduction velocity has been shown to be proportional to the square root of longitudinal resistance. A major determinant of longitudinal resistance in myocardium is the gap junction channel, comprised connexin proteins. Within the ventricular myocardium connexin43 (Cx43) is the dominantly expressed connexin. Reduced numbers of gap junction channels will result in an increase in longitudinal resistance creating the possibility of slowed conduction velocity while increased numbers of channels would potentially result in an increase in conduction velocity. We sought to determine if inhibition of histone deacetylase (HDAC) by 4-phenylbutyrate (4-PB), a known inhibitor of HDAC resulted in an increase in junctional conductance and permeability, which is not the result of changes in single channel unitary conductance. These experiments were performed using HEK-293 cells and HeLa cells stably transfected with Cx43. Following treatment with increasing concentrations of 4-PB up-regulation of Cx43 was observed via Western blot analysis. Junctional (gj) conductance and unitary single channel conductance were measured via whole-cell patch clamp. In addition intercellular transfer of lucifer yellow (LY) was determined by fluorescence microscopy. The data in this study indicate that 4-PB is able to enhance functional Cx43 gap junction coupling as indicated by LY dye transfer and multichannel and single channel data along with Western blot analysis. As a corollary, pharmacological agents such as 4-PB have the potential, by increasing intercellular coupling, to reduce the effect of ischemia. It remains to be seen whether drugs like 4-PB will be effective in preventing cardiac maladies.